Genetic structure and evidence of anthropogenic effects on wild populations of two Neotropical catfishes: baselines for conservation. Issue 1 (20th November 2017) - Do Prado, F. D.; Fernandez‐Cebrián, R.; Foresti, F.; Oliveira, C.; Martínez, P.; Porto‐Foresti, F.
Abstract : Genetic diversity and structure of Pseudoplatystoma corruscans and P. reticulatum, large migratory South America catfishes, where overfishing and the construction of numerous dams in their feeding and reproducing areas are affecting their migratory processes negatively, were studied using microsatellites in samples from Paraguay (that comprises the Pantanal biome), and the upper and lower Paraná Basins. Genetic diversity was in accordance to that observed for other large migratory fishes, but the most geographically isolated populations of P. reticulatum and those P. corruscans subject to anthropogenic effects (stocking and dams) showed lower genetic diversity and evidences of bottlenecks compatible with low effective population size. Pseudoplatystoma reticulatum presented subtle genetic differentiation within the Paraguay area, especially between the edges of its distribution. Pseudoplatystoma corruscans, in this same area, presented a quite homogeneous but significant genetic break between the Paraguay and upper Paraná populations, apparently resulting from natural and historical isolation between the basins until recently. These data demonstrates that, although these Pseudoplatystoma spp. are abundant in the Pantanal area, anthropogenic events are leading to negative effects on their populations, particularly in the upper Paraná Basin. Genetic differentiation observed along each species distribution demands conservation actions to preserve each population's biodiversity. These results represent important genetic information using new microsatellite markers and the first genetic study of P. reticulatum covering this area of its native distribution. Data may also contribute to a better understanding of species migration patterns and to be used as a baseline for proper management.